You get what you expect? A critical appraisal of imaging methodology in endosonographic cancer staging. Issue 5 (1st May 2002) - Meining, A; Dittler, H J; Wolf, A; Lorenz, R; Schusdziarra, V; Siewert, J-R; Classen, M; Höfler, H; Rösch, T
Abstract : Background and aims: After an initial period of excellent results with newly introduced imaging procedures, the accuracy of most imaging methods declines in later publications. This effect may be due to various methodological factors involved in the research. Using the example of endoscopic ultrasound (EUS), this study aimed to elucidate one of the factors possibly concerned—namely, the extent to which the examiners are adequately blinded. Methods: Well documented videotapes of EUS examinations of 101 patients with resected tumours of the oesophagus (n=32), stomach (n=33), or pancreas (n=36) were evaluated in three different ways: firstly, retrospective analysis under routine clinical conditions; secondly, evaluation of EUS videotapes in a strictly blinded fashion; and thirdly, evaluation of the same videotapes but with additional information from the video endoscopic appearance (oesophageal/gastric cancer) or from computed tomography results (pancreatic cancer). Histopathological T staging was used as the reference method. Results: The accuracy of EUS in T staging was 73% under routine conditions. This value fell significantly to 53% for the blinded evaluation but increased again to 62% for the unblinded evaluation. The sensitivity of staging T1/T2 tumours was 72% (routine EUS), 59% (blinded EUS), and 70% (unblinded EUS). The respective values for advanced tumours were 85%, 74%, and 72%. Conclusions: The accuracy of EUS for T staging in clinical practice appears to be lower than has previously been reported. In addition, blinded analysis produced significantly poorer results, which improved when another test was added. It may be speculated that better results with routine EUS obtained in a clinical setting are due to additional sources of information.